Genetic Variation May Have Promoted the Successful Colonization of the Invasive Gall Midge, Obolodiplosis robiniae, in China - Yao, Yan-Xia; Shang, Xing-Pu; Yang, Jun; Lin, Ruo-Zhu; Huai, Wen-Xia; Zhao, Wen-Xia (Frontiers in Genetics, 2020)
Invasive species often cause serious economic and ecological damage. Despite decades of extensive impacts of invasives on bio-diversity and agroforestry, the mechanisms underlying the genetic adaptation and rapid evolution of invading populations remain poorly understood. The black locust gall midge, Obolodiplosis robiniae, a highly invasive species that originated in North America, spread widely throughout Asia and Europe in the past decade. Here, we used 11 microsatellite DNA markers to analyze the genetic variation of 22 O. robiniae populations in China (the introduced region) and two additional US populations (the native region). A relatively high level of genetic diversity was detected among the introduced populations, even though they exhibited lower diversity than the native US populations. Evidence for genetic differentiation among the introduced Chinese populations was also found based on the high Fst value compared to the relatively low among the native US populations. Phylogenetic trees, structure graphical output, and principal coordinate analysis plots suggested that the Chinese O. robiniae populations (separated by up to 2,540 km) cluster into two main groups independent of geographical distance. Genetic variation has been observed to increase rapidly during adaptation to a new environment, possibly contributing to population establishment and spread. Our results provide insights into the genetic mechanisms underlying successful invasion, and identify factors that have contributed to colonization by an economically important pest species in China. In addition, the findings improve our understanding of the role that genetic structure plays during invasion by O. robiniae.